2022
DOI: 10.1186/s43088-022-00296-y
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as dual inhibitors of cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LOX): molecular docking and in vitro studies

Abstract: Background Inflammation is known to involve in many pathological processes of different diseases, but the current therapy causes adverse effects. Thus, there is a great interest for the discovery of flavonoids as a valuable alternative to classical analgesic and anti-inflammatory agent with dual-inhibitory action, especially on both COX-2 and 5-LOX which can minimize or overcome this problem. Results In the present work, drug-likeness properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Moreover, the strong binding affinity could be attributed to the presence of polar residues, namely Arg120, Ser353, Tyr385, Gly526, and Glu524 that enhance the chances of squeezing the molecule into the active site. To sum up, curcumin’s selectivity to COX-2 was primarily due to the binding to the hydrophobic region and extending to the lobby region near the entrance of the COX-2 binding site, thereby forming hydrogen bonds with Ser530 69 . Moreover, the position of the co-crystallized ligand and the three test compounds inside the catalytic site of COX-2 was stabilized by surrounded hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the strong binding affinity could be attributed to the presence of polar residues, namely Arg120, Ser353, Tyr385, Gly526, and Glu524 that enhance the chances of squeezing the molecule into the active site. To sum up, curcumin’s selectivity to COX-2 was primarily due to the binding to the hydrophobic region and extending to the lobby region near the entrance of the COX-2 binding site, thereby forming hydrogen bonds with Ser530 69 . Moreover, the position of the co-crystallized ligand and the three test compounds inside the catalytic site of COX-2 was stabilized by surrounded hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Ser353, Tyr355, Tyr385, Ser530, Gly526, and Glu524. This encloses the curcumin molecule in a cage-like structure, justifying its COX-1 inhibition and increasing its selectivity 69 . Capsaicin and gingerol displayed less binding energies and interactions with the COX-1 binding site.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studied compounds and following the docking carried out using AutoDock Vina, the authors identified some polyphenols as promising binders [ 45 ]. This aspect was also described by Idris et al in their contribution in which they investigated polyphenols as ligands for 5-LOX and COX-2 [ 46 ]. For example, quercetin, which is present in U. dioica also in its glycosylated forms, was highlighted as a potential interactor of 5-LOX and COX-2 with anti-inflammatory activity [ 47 ].…”
Section: The Neuroprotective Potential Of U Dioicamentioning
confidence: 62%
“…Prostaglandin synthesis is known to be inhibited by flavonoids. 25 As such, the polyphenols that have been reported in the leaves of V. auriculifera might be responsible for the demonstrated anti-inflammatory and analgesic effects. 14 , 26 In the cotton pellet-induced granuloma model, ME, MEF, and AQF inhibited both exudate and granuloma formation at all investigated concentrations.…”
Section: Discussionmentioning
confidence: 99%